The examination of elementary mathematics pre-service teachers' spatial abilities - ÖZDEMİR, AHMET ŞÜKRÜ (ELSEVIER SCIENCE BV, 2015)
The purpose of this study is to analyze the spatial abilities of pre-service mathematics teachers according to SOLO taxonomy. For this purpose, three students with different spatial skills were selected and clinical interviews were carried out with these students. The data was evaluated qualitatively and analyzed descriptively. A section was created for each of the answers given by students. In addition to that direct quotations from the dialogues were also used. The data collected shows that as the spatial skills of pre-service teachers increase their reasoning skills also increase. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: spatial skills; SOLO taxonomy; descriptive analysis